The rationing of nursing care phenomenon in the light of scientific reports - definitions, system solutions, assessment methods - PART I - Dorota Milecka; Henryka Homętowska; Stanisław Manulik (Kazimierz Wielki University, 2023)
Rationing of nursing care is a widespread and growing phenomenon whose causes are multifaceted and whose consequences are serious. Nursing rationing is defined as withholding or failing to perform necessary nursing tasks due to insufficient time, staffing, and/or inadequate skills. Nursing rationing is also defined as omission, delay, or failure to complete, which qualifies as an error of omission. Unfinished nursing care has many negative consequences for patients, nurses, and organizations. The presented series of three papers aims to show many important aspects related to care rationing. This first part of the series of rationing of nursing care phenomenon will address definitions and concepts of rationing of nursing care, rationing of nursing care in the context of health care rationing, rationing of care versus omission of care or medical error, methods for assessing the rationing and the quality of nursing care, and main reasons for rationing of nursing care.